New structural and seismological evidence and interpretation of a lithospheric‐scale shear zone at the southern edge of the Ionian subduction system (central‐eastern Sicily, Italy). Issue 6 (22nd June 2016) - Barreca, G.; Scarfì, L.; Cannavò, F.; Koulakov, I.; Monaco, C.
Abstract: Geological, gravimetric, and seismological data from the central‐eastern Sicily (Italy) provide evidences of a NW‐SE oriented shear zone at the southern edge of the Ionian subduction system. This structure consists of a near 100 km long lithospheric‐scale structural and seismic boundary. In the near‐surface, it shows Plio‐Pleistocene vertical‐axis structural rotations, kilometer‐scale topographic imprint, progressive wrenching, and large down‐faulting. All these features, together with its location south‐west of the subduction system, allow us to interpret the shear zone as the upper plate expression of an abandoned Subduction Transform Edge Propagator fault, working before slab detachment, currently reactivated by elastic rebound or mantle upwelling mechanism triggered by slab detachment, to form an incipient transform belt separating compartments characterized by different motion in the modern context of Africa‐Europe convergence. Key Points: We performed an integrative analysis of geological gravimetric and seismological data Analyzed data depicted a not well‐known wrench zone in the central‐eastern Sicily Our findings enabled us to interpret this shear zone as a Plio‐Pleistocene STEP fault